The longest night - Braden, Kara (Sourcebooks Casablanca, 2014)
"When a car accident leaves gorgeous but prickly genius Ian Fairchild with a debilitating injury and an addiction to painkillers, this city boy has to find a safe place to recover. He escapes to the remote Canadian wilderness, as far from the lights of Manhattan as he can get-and in the company of a woman he has no reason to trust. Will they make it through the winter? Former Marine Captain Cecily Knight prides herself on being self-sufficient. Her nearest neighbor is miles away, she has to fly to town for basic necessities, and she can go weeks without seeing another soul ... and that's the way she likes it. But when she's called on to repay a debt, she agrees to allow Ian to stay with her in her isolated cabin, on one condition: just because he's invading her privacy doesn't mean she's willing to open herself up to him, even if he is as tempting as sin. But as they spend day after day in in the wilderness together, Cecily and Ian's wary friendship turns into a love these two lost souls needed more than they ever knew."--from publisher's description.